2009
DOI: 10.1037/a0017260
|View full text |Cite
|
Sign up to set email alerts
|

Rapid cognitive screening of patients with substance use disorders.

Abstract: To date, there has not been a time-efficient and resource-conscious way to identify cognitive impairment in patients with substance use disorders (SUD). The present study assesses the validity, accuracy, and clinical utility of a brief (10 min) screening instrument, the Montreal Cognitive Assessment (MoCA), in identifying cognitive impairment among SUD patients. The Neuropsychological Assessment Battery-Screening Module (NAB-SM), a 45-minute battery with known sensitivity to the mild-to-moderate deficits obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(118 citation statements)
references
References 62 publications
5
108
0
3
Order By: Relevance
“…Montreal of Cognitive Assessment [Copersino et al, 2009], University of California-San Diego Brief Assessment of Capacity to Consent [Jeste et al, 2007], or assessment by qualified judges [Pachet et al, 2010]), aiming to find precision in the classification of ineligible participants or to have ulterior control of effects of cognitive functioning on collected data.…”
Section: Discussionmentioning
confidence: 99%
“…Montreal of Cognitive Assessment [Copersino et al, 2009], University of California-San Diego Brief Assessment of Capacity to Consent [Jeste et al, 2007], or assessment by qualified judges [Pachet et al, 2010]), aiming to find precision in the classification of ineligible participants or to have ulterior control of effects of cognitive functioning on collected data.…”
Section: Discussionmentioning
confidence: 99%
“…MOCA or Addenbrookes') (Copersino et al, 2009; Rojo-Mota, Pedrero-Perez, Ruiz-Sanchez de Leon, Llanero-Luque & Puerta-Garcia, 2013), and there is a great amount of evidence on screening for cognitive impairment in acquired brain damage (stroke, traumatic brain injury, HIV). But there is a shortage of literature about cognitive screening in alcoholism.…”
Section: Neurocognitive Evaluation In Alcohol Use Disorders: Challengesmentioning
confidence: 99%
“…The MoCA takes 15 minutes to administer, is a free resource (Nasreddine, 2014), and can be administered by staff without formal neuropsychological training. Initial studies have found evidence supporting the use of the MoCA in AOD treatment settings (Copersino et al, 2009;Copersino et al, 2012).…”
Section: Introductionmentioning
confidence: 99%